Sonances and Dissonances: Listening to the Ukranian Soundscape in the Holodomor Context (1932-1933) - Vasquez Zarate, G. Angelica (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The article presents the reconstructed soundscape in the context of the artificial famine (Holodomor) unleashed in Ukraine (1932-1933), this was carried out from the hermeneutic analysis of the testimony published by Miron Dolot, called Execution by Hunger, the Hidden Holocaust. The results of the study show the Bolsheviks altered the sound environment of the victim’s place of residence, during the land collectivization process. They had the purpose of establishing a new pattern of behavior and turning an unknown territory into a recognizable one, and capable of being possessed, in order to give rise to a universal subject, devoid of history, social class and ethnic identity, who will act under the values and ideals promoted by the Soviet socialist society.